School leadership and intercultural understanding: school foyers as situated spaces for doing diversity. Issue 9 (2nd September 2017) - Moss, Julianne; O'Mara, Joanne; McCandless, Trevor
ABSTRACT: Internationally, Intercultural Understanding (ICU) is increasingly prevalent in the field of education. The recent evidence base includes a growing academic literature and examples of specified education policy and curricula. In regards to leveraging ICU, research suggests a multi-level and longitudinal approach is needed to ensure effective and sustainable school change. Significant gaps exist in the literature about the contextual factors across all school levels that facilitate or impede the development of ICU. These gaps include research and action pertaining to school leadership. This paper draws from interviews and visual data generated in a large Australian study and focuses on the centrality of a single architectural feature of the school, the school foyer, and how principals grapple with the (re)design of these spaces to assert themselves as interculturally capable schools. Discourses of educational leadership have historically relied on well-worn leadership models of operational practices rather than explicitly framing an understanding of diversity to support intercultural capabilities. During a period of mandated Australian curriculum reform and assessment, this paper offers another way of 'Doing Diversity' of interest to policy makers and school leadership keen to embed ICU in their schools while highlighting the significant role school leaders have in progressing ICU.